Effect of Iron Supplementation on Haemoglobin Levels in Anaemic Children of 2–5 Years Age Group (Community Based Medical Journal, 2025)
Iron-deficiency anaemia is a major health issue among young children in low-resource settings, contributing to developmental delays and increased morbidity. A randomized controlled trial was conducted at Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, from January 2022 to December 2023,  to assess the effect of iron supplementation on haemoglobin levels in anaemic children of 2–5 years age group. A total of 60 anaemic children with haemoglobin